2005
DOI: 10.1002/ijc.21288
|View full text |Cite
|
Sign up to set email alerts
|

H2 relaxin overexpression increases in vivo prostate xenograft tumor growth and angiogenesis

Abstract: Our study reports a preliminary investigation into the role of human H2 relaxin in prostate tumor growth. A luciferase-expressing human prostate cancer cell line, PC-3, was generated and termed PC3-Luc. PC3-Luc cells were transduced with lentiviral vectors engineering the expression of either enhanced green fluorescent protein (eGFP) or both H2 relaxin and eGFP in a bicistronic format. These transduced cells were termed PC3-Luc-eGFP and PC3-Luc-H2/eGFP, respectively. To gauge effects, PC3-Luc-H2/eGFP and PC3-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
3
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 50 publications
(73 reference statements)
6
91
3
2
Order By: Relevance
“…The polypeptide hormone H2-relaxin (RNL2) is increased in human carcinoma and is associated with increased migratory capacity of carcinoma cells of the breast (37,38), prostate (39), and thyroid (10). We showed that RLN2 enhances cell motility and matrix invasion of human thyroid carcinoma cells and this action requires functional RXPF1 signaling (10).…”
Section: Discussionmentioning
confidence: 98%
“…The polypeptide hormone H2-relaxin (RNL2) is increased in human carcinoma and is associated with increased migratory capacity of carcinoma cells of the breast (37,38), prostate (39), and thyroid (10). We showed that RLN2 enhances cell motility and matrix invasion of human thyroid carcinoma cells and this action requires functional RXPF1 signaling (10).…”
Section: Discussionmentioning
confidence: 98%
“…We have studied the tumorigenic effect of RLN, a small peptide hormone produced both in the normal prostate and in prostate cancer (Figueiredo et al 2005, Silvertown et al 2006, Thompson et al 2006, Vinall et al 2006, Feng et al 2007, Liu et al 2008. Previously it has been shown that the RLN expression was increased in aggressive metastatic disease (Figueiredo et al 2005, Thompson et al 2006, Feng et al 2007, and that the stimulation of prostate cancer cells with RLN accelerated their invasiveness, adhesion, survival, and decreased cell apoptosis (Feng et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant variations in the amino acid sequence of different mammalian RLN peptides, they all efficiently cross-activate human RXFP1 (Sherwood 2004, Bathgate et al 2006. Recently, it was demonstrated that an analog of RLN peptide with a mutated receptor-binding domain has a moderately suppressive effect on prostate tumor when stably or transiently expressed in prostate cancer cells (Silvertown et al 2006). With apparent limitations of an overexpression approach in mind, we decided to investigate the effect of direct RXFP1 knockdown in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations